Artemisia Species as a New Candidate for Diabetes Therapy: A Comprehensive Review - Sharafati-Chaleshtori, Reza; Nickdasti, Ali; Mortezapour, Erfan; Pourhanifeh, Mohammad H.; Ghazanfari, Mohsen; Movahedpour, Ahmad; Khatami, Alireza; Ashrafizadeh, Milad; Zarrabi, Ali; Mahabady, Mahmood Khaksary; Khani, Haroon; Mirzaei, Hamed (Current Molecular Medicine, 2021)
Diabetes mellitus (DM) is a chronic disease and a threatening problem for world health. Allopathic medications are not efficient enough in controlling DM and its complications. Therefore, much attention has been directed towards the traditional medicine system. Plant derived-natural compounds with medicinal properties play an essential role in DM management and treatment. Artemisia is a varied and widespread genus of the family Asteraceae, which has more than 500 species with beneficial economic and therapeutic significance. Electronic databases such as Science Direct, Scopus, Pubmed, Web of Science, medRixv, and Wiley were used to search scientific literature. In folklore medicine, Artemisia species have been widely utilized for diabetes management. Molecular investigations have revealed that the NF-ΚB suppression, Notch 1 inhibition, cell cycle stop at S+G2/M-phase, enhanced Bax protein concentrations, mitochondrial membrane potential attenuation, activation of p53 and caspase, Bcl-2 regulation, and ROS formation are crucial mechanisms that could be targeted via various Artemisia species. Anti-diabetic effects of single or multiple doses of alcoholic and aqueous extracts of Artemisia species are due to the presence of bioactive compounds, and they are completely efficient in lowering levels of blood glucose in experimental examinations. In spite of the available anti-diabetic drugs, therapeutic agents obtained from the mentioned plants have been used for the treatment of this disease and its complications with less adverse impacts. Taken together, multiple lines of evidence indicated that Artemisia species could be introduced as a potential therapeutic candidate in the treatment and management of diabetes.
Keywords: Asteraceae